2020
DOI: 10.1038/s42255-020-0238-1
|View full text |Cite|
|
Sign up to set email alerts
|

Altered proximal tubular cell glucose metabolism during acute kidney injury is associated with mortality

Abstract: Acute Kidney Injury (AKI) is strongly associated with adverse outcome and mortality independently of the cause of renal damage [1][2][3] . The mechanisms determining the deleterious systemic effects of AKI are poorly understood and specific interventions, including optimization of renal replacement therapy, had a marginal effect on AKI-associated mortality in clinical trials [4][5][6][7][8] . The kidney contributes to up to 40% of systemic glucose production by gluconeogenesis during fasting and stress conditi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
137
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(153 citation statements)
references
References 58 publications
(38 reference statements)
9
137
1
Order By: Relevance
“…However, even regenerating tubules present increased glycolytic enzyme expression, and this irreversibility of metabolic profile led the cell to hypoxia and induced the profibrotic signaling (Lan et al, 2016), which can contribute to the progression from AKI to chronic pathology. In line with this, it was observed an increase in glycolytic profile in experimental and clinical AKI, in contrast with the reduction of gluconeogenesis (Legouis et al, 2020). It was observed that rate-limiting gluconeogenesis enzymes were decreased during the early phase following ischemia-reperfusion injury, but the expression of glycolytic enzymes was increased.…”
Section: Kidney Dysfunction and Metabolismsupporting
confidence: 57%
See 3 more Smart Citations
“…However, even regenerating tubules present increased glycolytic enzyme expression, and this irreversibility of metabolic profile led the cell to hypoxia and induced the profibrotic signaling (Lan et al, 2016), which can contribute to the progression from AKI to chronic pathology. In line with this, it was observed an increase in glycolytic profile in experimental and clinical AKI, in contrast with the reduction of gluconeogenesis (Legouis et al, 2020). It was observed that rate-limiting gluconeogenesis enzymes were decreased during the early phase following ischemia-reperfusion injury, but the expression of glycolytic enzymes was increased.…”
Section: Kidney Dysfunction and Metabolismsupporting
confidence: 57%
“…The reduction of renal gluconeogenesis can contribute to hypoglycemia in stress conditions, compromising the systemic metabolism and contributing to worsening patient condition. Metabolic reprogramming of glucose metabolism during AKI was associated with mortality, as reported by Legouis et al (2020). COVID-19 patients with metabolic disorders have a worsening of the clinical condition associated with acute kidney disease, which suggests that dysfunction in systemic metabolism may contribute to renal injury in COVID-19.…”
Section: Kidney Dysfunction and Metabolismmentioning
confidence: 74%
See 2 more Smart Citations
“…Legouis et al have recently shown that AKI leads to increased glycolysis and reduced gluconeogenesis in the kidney, which together lead to lactate accumulation and a decrease in systemic glucose levels. AKI‐associated mortality was reduced when glucose metabolism was restored by thiamine supplementation, thereby demonstrating the need to explore metabolic disturbances in AKI as new areas for therapeutic intervention [48].…”
Section: Discussionmentioning
confidence: 99%